Bahasa Indonesia: Bahasa Indonesia - salsabila, noviana (Jurnal Penjaminan Mutu, 2025)
This study aims to analyze the impact of implementing differentiated instruction in Social Studies learning at MTs Tribakti Singosari using a descriptive qualitative approach. Differentiated instruction was applied to accommodate students’ needs, interests, and learning profiles in Social Studies, a subject characterized by complex content and the need for contextual understanding. Data were collected through observations, interviews, and documentation, then analyzed using data reduction, data display, and conclusion-drawing techniques. The findings indicate that differentiated instruction has a positive impact on increasing student participation, learning motivation, and conceptual understanding. Adjustments in learning content, processes, and products enable students to learn according to their individual abilities, making the classroom more inclusive and interactive. Furthermore, teachers are better able to identify students’ learning needs and provide more personalized support. Nevertheless, several challenges remain, including limited instructional time, a wide range of student ability levels, and teachers’ readiness to consistently design differentiated learning materials. Overall, differentiated instruction contributes significantly to improving the quality of Social Studies learning and is worthy of continuous development.